Design of asymmetrical resonator for microstrip triple-band and broadband bandpass filters. Issue 12 (December 2015) - Hsu, Ko-Wen; Tu, Wen-Hua
Abstract: This paper presents two triple-band bandpass filters (BPFs) and one broadband BPF by using asymmetrical resonators. The asymmetrical resonator consists of three branched microstrip sections with different electrical lengths. For the first triple-band BPF (Filter I), by adjusting the stub length of the resonator, the first three resonant modes can be moved to the required center frequencies. For the second triple-band BPF (Filter II), the two sets of asymmetrical resonators are designed with the characteristic of the same center frequencies and staggered higher-order modes to achieve a wide stopband. For the broadband BPF (Filter III), the multi-mode resonances and inherent transmission zeros of the asymmetrical resonator are utilized to design the wideband response with sharp passband selectivity. It has the advantages of compact size and harmonic suppression.